1983
DOI: 10.1210/jcem-57-3-627
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Vitamin D Metabolites by Human Melanoma Cells*

Abstract: Two melanin-producing human melanoma cell lines originally established from fresh surgical specimens were incubated with 25 hydroxyvitamin D3 (25 OHD3). Both cell lines produced material comigrating with 1,25 dihydroxy-vitamin D3 (1,25(OH)2D3) and 24,25 dihydroxyvitamin D3 (24,25(OH)2D3) in straight and reverse phase high performance liquid chromatography systems and displacing the relevant labeled ligands in competitive binding assays. The material designated 1,25(OH)2D3 was found almost entirely within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Although it is clear that the kidney is the main site of production of l,25(OH)2D3, cell lines de¬ rived from bone (Howard et al 1981) and skin (Frankel et al 1983) have demonstrable activities of the 25(OH)D3-l-hvdroxvlase enzyme. Indeed, low plasma concentrations of 1,25(OH)2D3 have been demonstrated in anephric patients (Lambert et al 1982), and it has been suggested that granulomatous tissue mav be a site of l,25(OH)2D3 synthesis (Barbour et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that the kidney is the main site of production of l,25(OH)2D3, cell lines de¬ rived from bone (Howard et al 1981) and skin (Frankel et al 1983) have demonstrable activities of the 25(OH)D3-l-hvdroxvlase enzyme. Indeed, low plasma concentrations of 1,25(OH)2D3 have been demonstrated in anephric patients (Lambert et al 1982), and it has been suggested that granulomatous tissue mav be a site of l,25(OH)2D3 synthesis (Barbour et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…239 This observation was supported by the description of vitamin D metabolism in melanoma cells. 240,241 Further studies showed that vitamin D inhibited the growth of several melanoma cell lines, including: human: A375, 242 ME18, 243 MeWo, 244246 RPMI 7951, 247,248 SK Mel 28, 247,249,250 SKMEL-188, WM35 and WM1341; 39,40,64,118,119,242,251 mouse B16; 67,252,253 and hamster Bomirski melanomas. 67,118 Furthermore, 1,25(OH) 2 D3 inhibited anchorage-independent growth and plating efficiency of human SKMEL-188, hamster AbC1, 39,64,118 and murine B16 (ref.…”
Section: Vitamin D and Experimental Models Of Melanomamentioning
confidence: 99%
“…Moreover, several anticancer mechanisms of calcitriol have been demonstrated, including local production of calcitriol by tumor cells (Frankel et al, 1983), with calcitriol resulting in increased tumor cell differentiation (Mason et al, 1988), increased tumor cell apoptosis (Ravid et al, 1999) and reduced tumor-induced angiogenesis (Majewski et al, 1996).…”
Section: Non-classical Effects Of Vitamin Dmentioning
confidence: 99%